Stomatal Closure and SA-, JA/ET-Signaling Pathways Are Essential for Bacillus amyloliquefaciens FZB42 to Restrict Leaf Disease Caused by Phytophthora nicotianae in Nicotiana benthamiana - Wu, Liming; Huang, Ziyang; Li, Xi; Ma, Liumin; Gu, Qin; Wu, Huijun; Liu, Jia; Borriss, Rainer; Wu, Zhen; Gao, Xuewen (Frontiers in Microbiology, 2018)
Bacillus amyloliquefaciens FZB42 is a plant growth-promoting rhizobacterium that induces resistance to a broad spectrum of pathogens. This study analyzed the mechanism by which FZB42 restricts leaf disease caused by Phytophthora nicotianae in Nicotiana benthamiana. The oomycete foliar pathogen P. nicotianae is able to reopen stomata which had been closed by the plant innate immune response to initiate penetration and infection. Here, we showed that root colonization by B. amyloliquefaciens FZB42 restricted pathogen-mediated stomatal reopening in N. benthamiana. Abscisic acid (ABA) and salicylic acid (SA)-regulated pathways mediated FZB42-induced stomatal closure after pathogen infection. Moreover, the defense-related genes PR-1a, LOX, and ERF1, involved in the SA and jasmonic acid (JA)/ethylene (ET) signaling pathways, respectively, were overexpressed, and levels of the hormones SA, JA, and ET increased in the leaves of B. amyloliquefaciens FZB42-treated wild type plants. Disruption of one of these three pathways in N. benthamiana plants increased susceptibility to the pathogen. These suggest that SA-and JA/ET- dependent signaling pathways were important in plant defenses against the pathogen. Our data thus explain a biocontrol mechanism of soil rhizobacteria in a plant.